Potential and Limitation of the Kumbhalgarh Wildlife Sanctuary for Sustainable Tiger Habitat - Verma, Lalit Mohan; Singh, Bhanwar Vishvendra Raj (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
The sustainability of tiger habitats is critical to the long-term survival of the species and the preservation of biodiversity-rich ecosystems. This study evaluates the potential and limitations of the Kumbhalgarh Wildlife Sanctuary (KWS) in Rajasthan, India, as a sustainable habitat for tigers. Using an integrated methodology combining SWOT analysis, geospatial tools (NDVI, LULC, DEM, slope, aspect, and drainage), and secondary data sources, the research identifies key ecological, geographical, and socio-economic factors influencing habitat viability. The results highlight significant strengths, including diverse landscapes, prey availability, legal protection, and increasing community awareness. However, limitations such as habitat fragmentation, seasonal water scarcity, human-wildlife conflict, and inadequate infrastructure pose challenges to tiger conservation. Strategic interventions formulated through the TOWS matrix suggest targeted approaches like habitat restoration, corridor development, eco-tourism, and technological monitoring. The study concludes that while KWS holds substantial potential, a coordinated and adaptive management framework is essential to overcome existing limitations and establish the sanctuary as a viable and sustainable habitat for tigers.